2017
DOI: 10.20867/tosee.04.2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Destination’s Tourism Offering in the Off-Season

Abstract: Purpose -This paper presents tourist attitudes regarding the off-season tourism offering of Rijeka and the Opatija Riviera, a seaside destination hosting about 2.2 million overnight stays per year. Since more than 54% of these stays are concentrated in the summer season, the destination is facing an issue of high seasonality. Therefore, an active approach is required that would result in higher tourist satisfaction in the off-season and bring about seasonality smoothing. Thus, the primary purpose of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The GA-IPA was completed by determining the differences between the performance and importance rankings (i.e., Gap = Performance − Importance) by each participant for each attribute, checking that the performance gaps for all participants approximated a normal distribution for each attribute, calculating the mean of the gaps for each PGI attribute, and checking if the mean gap for all responses was significantly different from zero (i.e., Performance = Importance) using a one sample t-Test [22,23,27]. Consistent with to the approach of Smolčić Jurdana et al [24][25][26] and Taplin [27], this study presents both the IPA grid for the DC-IPA and the GA-IPA on the same figure provided in the Results. The greater the gap in the performance of an attribute, which is represented by its distance from the line of parity (Performance = Importance) in the graphical representation, the higher the management priority to implement corrective action [18,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GA-IPA was completed by determining the differences between the performance and importance rankings (i.e., Gap = Performance − Importance) by each participant for each attribute, checking that the performance gaps for all participants approximated a normal distribution for each attribute, calculating the mean of the gaps for each PGI attribute, and checking if the mean gap for all responses was significantly different from zero (i.e., Performance = Importance) using a one sample t-Test [22,23,27]. Consistent with to the approach of Smolčić Jurdana et al [24][25][26] and Taplin [27], this study presents both the IPA grid for the DC-IPA and the GA-IPA on the same figure provided in the Results. The greater the gap in the performance of an attribute, which is represented by its distance from the line of parity (Performance = Importance) in the graphical representation, the higher the management priority to implement corrective action [18,22].…”
Section: Discussionmentioning
confidence: 99%
“…A number of techniques may be utilized when interrogating the collected information as described above, pursuant to improving on-ground management of urban PGI. While techniques of Importance-Performance Analysis (IPA) are widely applied to determine how well the attributes of a good or service perform in meeting the expectations of consumers, clients, users, and visitors (e.g., [18,[20][21][22][23][24][25][26][27], IPA has only rarely been applied to enhancing PGI management [18,28]. The literature review of Parker and Simpson [28,29] and additional research in support of this case study, identified only four other studies that have utilized IPA techniques to investigate how PGI users perceive urban PGI spaces [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…an ecotourism experience) meet the expectations of visitors (Smol ci c Jurdana and Soldi c Frleta, 2011;Soldi c Frleta, 2014;Sá nchez-Rebull et al, 2018). Visitors who are satisfied with their wildlife tourism experience are more likely to re-visit or recommend the experience to family or friends through word of mouth and, evermore commonly, through online platforms such as Facebook, Instagram and TripAdvisor (Gier et al, 2017;Smol ci c Jurdana et al, 2017;Prakash et al, 2019;Patroni et al, 2019). Satisfied visitors are essential for the future viability of an ecotourism operation/experience, because the income from tourists is vital for funding the operation, and having satisfied visitors can make these experiences more ecologically, economically and socially sustainable (Wilson and Tisdell, 2003;Schleimer et al, 2015;Patroni et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of visitor satisfaction for the ecotourism industry, within which wildlife tourism is a niche market segment, is summarised by Newsome et al (2013, p. 23) who wrote “Satisfaction of visitors with the ecotourism experience is essential to the long-term viability of the ecotourism industry […] and satisfaction should be second only to the conservation and protection of the resources on which tourism is based.” Visitor satisfaction is a measure of how well the attributes of a product or service (i.e. an ecotourism experience) meet the expectations of visitors (Smolčić Jurdana and Soldić Frleta, 2011; Soldić Frleta, 2014; Sánchez-Rebull et al , 2018). Visitors who are satisfied with their wildlife tourism experience are more likely to re-visit or recommend the experience to family or friends through word of mouth and, evermore commonly, through online platforms such as Facebook, Instagram and TripAdvisor (Gier et al , 2017; Smolčić Jurdana et al , 2017; Prakash et al , 2019; Patroni et al , 2019).…”
Section: Introductionmentioning
confidence: 99%